2007
DOI: 10.1016/j.placenta.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expression and Localisation of the Na+/H+ Exchanger (NHE) 3 and the NHE Regulatory Factor 2 in Baboon Placental Syncytiotrophoblast by Oestrogen

Abstract: Our understanding of the regulation of the expression of the sodium hydrogen exchangers (NHE) and their regulatory factors (NHERF), which play important roles in fetal-placental homeostasis, is incomplete. We previously showed that the expression and localization of NHE3 and NHERF2 in the juxtanuclear compartment of the placental syncytiotrophoblast were markedly decreased between mid and late baboon pregnancy. In the current study, immunocytochemical fluorescence localization and level of NHE3/NHE1 and NHERF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Fetal-to-placental weight ratio has been suggested to be indicative of placental efficiency (46). Indeed, our laboratory (41) has shown that estrogen suppression causes a change in expression and localization within the baboon placental syncytiotrophoblast of the sodium-hydrogen exchangers (NHE), which control solute and water flux. Therefore, the apparent increase in placental weight in estrogendeprived baboons may be due to an accumulation of fluid/water and perhaps cellular volume secondary to changes in placental expression of the NHE system.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal-to-placental weight ratio has been suggested to be indicative of placental efficiency (46). Indeed, our laboratory (41) has shown that estrogen suppression causes a change in expression and localization within the baboon placental syncytiotrophoblast of the sodium-hydrogen exchangers (NHE), which control solute and water flux. Therefore, the apparent increase in placental weight in estrogendeprived baboons may be due to an accumulation of fluid/water and perhaps cellular volume secondary to changes in placental expression of the NHE system.…”
Section: Discussionmentioning
confidence: 99%
“…The immunocytochemical detection of total ezrin, phosphorylated ezrin (T567), SLC9A3R1, and a-actinin was determined essentially as described previously [17,18]. Briefly, paraffin-embedded sections (4 lm) of fetal ovaries were mounted onto Superfrost/Plus microscope slides (Erie Scientific, Portsmouth, NH), heat fixed and, for diaminobenzidine (DAB) detection, endogenous peroxidase blocked with 0.3% H 2 O 2 (Sigma-Aldrich Corp., St. Louis, MO) in methanol (Fisher Scientific Co., Pittsburgh, PA).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…In select experiments, ovarian samples also were incubated with rabbit polyclonal antibody to GAPDH (0.75 lg/ml; Abcam Inc., Cambridge, MA) to correct for loading/transfer. Membranes were washed and incubated with anti-mouse (a-actinin), anti-goat (ezrin), or anti-rabbit (SLC9A3R1, GAPDH) IgG horseradish peroxidase-conjugated secondary antibody (Vector Laboratories) diluted (1:20 000) in Solution II, washed, and proteins detected using enhanced chemiluminescence (Amersham Biosciences, Pittsburgh, PA), as described previously [18]. Specificity of the primary antibodies was determined by incubation of samples without primary antibody.…”
Section: Immunocytochemistrymentioning
confidence: 99%